Innovation-Enhancing High-Performance Work Practices in Malaysian R&D Organizations: Myth Or Reality? - Mohd Hanafi, Mohd Shafiq; Asmawi, Arnifa; Chew, Kok Wai; Yang, Chia Yen (Universiti Utara Malaysia Press, 2024)
Numerous Malaysia policies underscore the need to build exceptional R&D capabilities as the key economic driver. This study acknowledges the influence of high-performance work practices (HPWP) on R&D innovativeness. Underpinned by social exchange theory, this study investigates the implementation of innovation-enhancing HPWP in Malaysian R&D organisations and their relationship with project performance. Survey data on R&D project performance and six dimensions of innovation-enhancing HPWP were collected from 210 project leaders and members. Results suggested that innovation-enhancing HPWP implementation is still low as HPWP might be a relatively unknown practice in the R&D sector. Nevertheless, four HPWP dimensions were significant predictors of R&D project performance: employee recruitment, performance appraisal, reward and compensation, and employee participation. These findings will guide managers in developing relevant HPWPs to foster innovativeness. This includes a comprehensive audit of existing R&D people, processes, and products, and how these three `Ps’ can be streamlined into an innovation-enhancing HPWP.